Potential Probiotic Bacillus Strains Isolated from Contaminated Soil in North Macedonia: Salmonella Growth Inhibition - Sofija Kostandinovska; Dzoko Kungulovski; Natalija Atanasova-Pancevska (Biology and Life Sciences Forum, 2023)
Salmonellosis, which occurs most frequently (85%) as a result of consuming contaminated food, is brought on by salmonellae, which are bacteria that can infect both humans and animals. The aim of this study was to investigate the probiotic properties of three Bacillus spp. strains isolated from contaminated soil in North Macedonia and their antimicrobial activity. Additionally, their ability to survive in the presence of bile salts and at low pH and their susceptibility to antibiotics were examined. This research indicates that new Bacillus strains’ probiotic qualities are also promising and exhibit strong inhibition activity against Salmonella enterica ATCC 10708.